Efforts in vain / Noraziah Mohd Amin - Mohd Amin, Noraziah (Academy of Language Studies, 2022)
Face is vacant, heart is silent A blatant existence is not important No more spotlight or the stage For wisdom grows with age So, you rather step to the side And put everything away and hide.